Association between traumatic dental injuries (TDIs) and caries experience in a selected northern Nigerian population - O.O. Taiwo (Nigerian Dental Association, 2014)
Objective: To determine the association between traumatic dental injuries (TDIs) and caries experience in a selected Nigerian population and the influence(s) of gender and location on this association. Method: The sample size included 799 school children proportionately selected through multistage sampling technique. Caries experience (DMFT) and TDIs to the teeth were evaluated clinically by one examiner (intra-examiner reliability was 0.852 by Cronbach's Alpha test). The TDIs were classified according to the modified Ellis classification. Diagnosis of caries was at cavitation level. Analysis was by the use of SPSS v17.0. Result: There were 450 (56.3%) males and 43.7% females. Subjects were aged 12 to 21 years (Mean 12.25 ± 0.93). About half (51.8%) were from the urban areas. Prevalence of TDIs and caries was 14.6% and 12.4% respectively. TDIs were more prevalent among males (P = 0.015, OR = 1.7, 95% CI = 1.103, 2.519), with enamel fracture (74.5%) being the commonest (74.5%) TDI seen. Dental caries was commoner in the rural areas (DMFT [ ] = 0.249, B = 0.029, 95% CI = -0.180, -0.009). There was no significant association between caries experience and TDIs ( = 0.197, p = 0.944, 95% CI = -0.125, 0.117) and neither by gender nor location (P>0.05). The odds of having TDIs in those with dental caries was 1.04, 95% CI = 0.581, 1.885. Conclusion: There was no association between TDIs and caries experience in the studied Nigerian population. Caries experience was more in the rural areas and being male was associated with a higher probability of having a traumatized tooth.